Highly selective detection of palladium ions by sulfur-containing tetraphenylethylene tetracycle helicate - Ye, Feng-Ying; Hu, Ming; Yu, Wei; Zheng, Yan-Song (Dyes and pigments, 2023)
As a very important noble metal, palladium has extensive application in alloy materials, catalysts, jewelry, and so on. Due to concern for the effect of the palladium ion on environment and human being health, the detection of the palladium is necessary. However, the analysis of the palladium ions with high selectivity and sensitivity is very rare. Here, we synthesized sulfur-containing tetraphenylethylene (TPE) tetracycle tetrathioether in high yield, which displayed aggregation-induced emission enhancement (AIEE) and 100% fluorescence quantum yield (ΦF) in the aggregation state. Exceptionally, when 21 kinds of metal ions were added into the TPE tetrathioether in THF solution, only palladium ions could quench the bright fluorescence of the TPE tetrathioether, displaying extremely high selectivity of the probe. Meanwhile, the interaction between palladium and TPE tetrathioether produced a white to black precipitate, enabling visual detection of the palladium ion. The limit of detection (LOD) was as low as 3.85 × 10−7 M, indicating a high sensitivity of probe. By the X-ray crystallographic analysis and NMR spectra, it was found that palladium ions could coordinate with four sulfur atoms in the caves of TPE tetrathioether at gem sites. The design of TPE macrocyclic thioether with quantitative ΦF provided a new approach to very high selective and sensitive probe, and even visual detection for palladium ions. [Display omitted] •New tetraphenylethylene macrocycle thioether with quantitative fluorescence quantum yield is synthesized.•The TPE macrocycle could include palladium ion in its cavity, showing highly selective and sensitive detection of palladium.•The detection of palladium ion can be visualized by naked eye because of color change besides fluorescence quenching.